The Soviet Union in the Sino-Vietnamese Strategic Triangle (1975–1979): A Structural Power and Strategic Perception Perspective - Luu Van Quyet; Vu Hung Phi (International Journal of Asia Pacific Studies, 2026)
Between 1975 and 1979, the strategic triangle involving Vietnam, China, and the Soviet Union (USSR) underwent a profound transformation that culminated in the 1979 Sino-Vietnamese border war. This study revisits that transformation by positioning the USSR not merely as a contextual backdrop but as a decisive source of structural power shaping both Vietnam’s strategic alignment and China’s threat perceptions. While existing scholarship has largely emphasised Chinese and Vietnamese motivations, this study places the Soviet dimension at the analytical centre as an independent variable. Integrating structural realism with strategic cognition, this study conceptualises structural power not simply as material capability but as the capacity to generate strategic effects through alliances, institutional linkages, and access arrangements that shape perceptions and expectations. Methodologically, this study draws on qualitative analysis of declassified archives, diplomatic correspondence, and contemporaneous Vietnamese, Soviet, Chinese, and Western sources. The findings suggest that although the USSR did not directly instigate the 1979 conflict, its strategic posture—symbolised by the 1978 Treaty of Friendship and Cooperation and access arrangements at Cam Ranh Bay—significantly intensified Beijing’s perception of strategic encirclement. Vietnamese official discourse generally interpreted Soviet commitments as political and strategic reassurance. Moscow, however, continued to employ deliberately ambiguous signalling. Here, ambiguity is understood as a strategic choice rather than a communication failure, contributing to widening gaps in strategic expectations within the triangle. This asymmetry of interpretation weakened deterrent stability and contributed to regional instability in late Cold War Southeast Asia.